New species of Tribonium Saussure from the State of Amazonas, Brazil (Blattaria, Blaberidae, Zetoborinae) - Lopes, Sonia Maria (Zootaxa, 2010)
The family Blaberidae contains large-sized species that may be apterous or subapterous with a rough pronotum, to fully winged with tegmina and wings extending beyond the apex of the abdomen. The family also contains small to medium-sized species colored green. Tribonium Saussure is placed in Zeborinae, one of the 10 subfamilies within Blaberidae (Roth 2003). Tribonium is essentially Neotropical, with species presenting a general brown coloration brown with dispersed black spots mainly on the tegmina. These similarities make species identifications difficult and further morphological studies of the genitalia are needed. Tribonium has a geographical distribution from French Guiana and Colombia to Brazil, Bolivia, Paraguay, and Argentina. The collection records are from tropical and subtropical forest, Atlantic forest, and regions of the Rio Grande do Sul. Currently, ten species are known, of which eight are Brazilian: T. conspersum (Guérin & Percheron), T. conspurcatum (Burmeister), T. delicatum Lopes, T. elegans (Brunner), T. gutulosum (Walker), T. litoris Lopes, T. neospectrum Lopes, and T. spectrum (Eschscholtz) (Lopes 1978).